2014
DOI: 10.1136/jramc-2014-000344
|View full text |Cite
|
Sign up to set email alerts
|

PTSD, stigma and barriers to help-seeking within the UK Armed Forces

Abstract: Among the general public, much is known about the longer-term consequences of not seeking support for mental health difficulties. However, within military populations, and in particular, the UK Armed Forces, less is known. Understanding the factors that present barriers for UK service personnel with mental health difficulties accessing support is important because this may provide a means for support personnel to seek help sooner. This paper explores the literature relating to the impact of untreated post-trau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 74 publications
(65 reference statements)
4
55
0
1
Order By: Relevance
“…Further, they were more likely to endorse barriers related to stigmatising beliefs than those related to practical access issues. This finding replicates similar research within military populations that reported a similar relationship [26,50,51]. …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Further, they were more likely to endorse barriers related to stigmatising beliefs than those related to practical access issues. This finding replicates similar research within military populations that reported a similar relationship [26,50,51]. …”
Section: Discussionsupporting
confidence: 91%
“…In the UK veteran population only around 25% of those with probable PTSD report seeking help [26,27]. These rates are not dissimilar to the rates of those who screen positive for PTSD seeking helping in the UK general public, European samples and US samples [28,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…90% in the UK military), the latter of these is unsurprising [18]. Further, evidence has emerged suggesting that there are many barriers that prevent veterans from engaging in help-seeking behaviours [19,20,21]. The former differences suggest that veterans in this sample may have had a longer history of alcohol abuse that was not detrimental to their employment status.…”
Section: Discussionmentioning
confidence: 96%
“…Given that there is evidence to suggest that only approximately 20% of veterans seek help for mental health and alcohol problems [20], this sampling strategy gave a unique insight into the alcohol-related needs of a sample of veterans and non-veterans who may not otherwise have come to the attention of traditional substance misuse services. Including all referrals over an 18 month period should improve the generalisability of our findings.…”
Section: Discussionmentioning
confidence: 99%
“…The first are related to practical barriers to accessing help, for example, lack of knowledge about available service and feeling that non-military specialist services are inappropriate or won’t be able to meet their needs 13. The second category is related to perceived negative stigmatisation or discrimination that could result from the disclosure of a mental health difficulty 14. Worryingly, there seems to be evidence showing that individuals who are experiencing mental health difficulties are also more likely to report a greater number of stigma-related barriers to engaging in help than individuals without difficulties 15…”
Section: Barriers To Seeking Helpmentioning
confidence: 99%